Effects of substituting alfalfa silage with whole plant quinoa silage on rumen fermentation characteristics and rumen microbial community of sheep in vitro - Jie Bai; Jie Bai; Lijuan Tang; Lijuan Tang; Mao Liu; Ting Jiao; Ting Jiao; Guiqin Zhao (Frontiers in Veterinary Science)
This study investigated the effect of different ratios of quinoa-to-alfalfa silage on the fermentation parameters, methane production, and rumen microbial community composition during in vitro fermentation trials. The objective was to evaluate the potential of quinoa as a viable silage material. Five treatment groups were set up with varying quinoa proportions of 0, 30, 50, 70, and 100%, and stored 60 days. The results showed that increasing the quinoa proportion in the alfalfa-quinoa mixed silage resulted in a decrease in concentrations of propionate, isobutyrate, isovalerate, and the methane (CH4) fraction of total gas emissions (p < 0.05). Conversely, dry matter digestibility, total volatile fatty acid (TVFA) concentration, acetate concentration, acetate to propionate ratio, butyrate concentration, cumulative CH4 emissions, and total gas production increased (p < 0.05). At the phylum level, the relative abundance of Spirochaetota decreased linearly (p < 0.05), while Verrucomicrobiota increased (p < 0.05). At the genus level, the relative abundance of CAG 873, Prevotella, Acinetobacter, Treponema D, RUG11690, and Ruminococcus E decreased linearly (p < 0.05), whereas the relative abundance of Bact 11, Limimorpha, F23 D06, Advenella, and unclassified bacteria increased linearly (p < 0.05). In summary, the inclusion of quinoa in alfalfa silage alters the fiber structure of the feed and significantly affects its nutritional composition, in vitro fermentation parameters, methane production, and microbial community composition. These findings offer valuable insights for optimizing ruminant feed.